Female teachers’ cartographies: the fourth dimension in mathematics education (Educação e Pesquisa, 2023)
This text moves the concept of cartography of devirings, geographies, directions, entrances, and exits, and lines of forces produced in two cartographic theses that present another possibility of thinking the formation of a mathematics teacher from its multiple subjectivities. In this writing, the idea is to provoke crossings that, from a cartographic exercise, create spaces that move practices and tactics of teachers, both in education and in mathematics education, that tension classroom relations and promote other visibilities, denaturalizing a certain school scenario. The conceptual appropriation of cartography is based on the philosophy of Gilles Deleuze and Félix Guattari, since these philosophers treat it as a practice of knowledge that provokes thinking forces that privilege difference as a product of itself. Cartography, through its intervention, allows a practice in which the subject can think/act on its own formation, a process that goes beyond discussions of school practices that only discuss methodologically the improvement of mathematics teaching. The concepts used allow for the invention of rhizome maps that draw paths with proposals that open a space for thinking about the multiple in teacher education, in school, and in mathematics education.